Vers une géographie imaginée de la Perse - Aurélie Choné (Recherches Germaniques)
Kurt Faber was born in Mulhouse in 1883. He interrupted his studies very early in order to satisfy his passion for travel. He passed the baccalauréat at a later stage, studied political science, worked as a journalist and became a member of the NSDAP in 1925. His travel narrative Mit dem Rucksack nach Indien (1927), which relates his journey from Vienna to India by land, via the Middle East, was published when he was 44 and at the height of his fame as a writer-traveler, and two years before he died of cold in Canada. Most of the book is devoted to Persia. My geopolitical reading dwells on Faber’s art of travel and sketches the outlines of the “imagined geography” of Persia that the narrative points out, especially through the importance it gives to some archetypal places. The study also analyses the situation of the traveler in a space characterized by its unbridgeable alterity, be it political or religious, but also its growing interactions with other cultures in a globalized world. This paper ultimately aims at accounting for Faber’s ambivalence, between the political convictions that led him to become a member of the NSDAP and the openness to the world he acquired through his journeys.